Factors Affecting the Entrepreneurial Interest of Gemah Ripah Milk Cooperative Members in Sukabumi - Sayekti, Ayutyas; Maulida, Maisya Salsa; Hernowo, Jarwadi Budi; Adji, Riyanto (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2025)
Low milk prices, the risk of returning milk for every member who does not meet the cooperative standard and cooperative members have little business are problems that occur at KPUD Gemah Ripah milk storage cooperative. This study aims to find out the indicators that affect each variable and identify the influence of variables of entrepreneurial spirit, motivation, capital, technical guidance, and marketing on entrepreneurial interest. The methods used in this study were multiple linear regression analysis and financial analysis with a sample of 109 people. The results of this study are indicators that affect the variables of the entrepreneurial traits such as being task oriented and result-oriented. The results of the study show that entrepreneurial spirit, motivation, capital, technical guidance and marketing have a positive and significant effect on the interest in entrepreneurship in members of the Gemah Ripah Cooperative partially or simultaneously. It is necessary to encourage in the form of training so that members of the Gemah Ripah KPUD have an interest in entrepreneurship